Let's get personal: predicting thiopurine and fluoropyrimidine toxicity. (November 2012) - Corrigan, Adele; Arenas-Hernandez, Monica; Blaker, Paul; Sanderson, Jeremy; Marinaki, Anthony
The US FDA now recognizes the need to individualize treatment paradigms using biomarkers that predict response to therapy. In clinical practice the best example of this is TPMT testing, which is used to rationalize the starting dose of azathioprine and mercaptopurine. The more recent addition of drug metabolite monitoring means that thiopurine therapy can now be personalized to unprecedented levels. Of interest, parallels exist between TPMT deficiency as an explanation for thiopurine toxicity and DPD deficiency in fluoropyrimidine toxicity. For these drugs, variations in a single locus predict severe toxicity. However, while TPMT testing has translated into routine clinical practice, DPD testing has not. This article summarizes the recent research investigating interindividual differences in the metabolism of thiopurine and fluoropyrimidine drugs, and explores the attitudes which influence the uptake of pharmacogenetic testing.